2020
DOI: 10.2337/figshare.12970550.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Empagliflozin on Obstructive Sleep Apnea, Cardiovascular, and Renal Outcomes: An Exploratory Analysis of the EMPA-REG OUTCOME Trial

Abstract: <b>Objective: </b>To explore the effects of empagliflozin on the incidence of obstructive sleep apnea (OSA) and its effects on metabolic, cardiovascular (CV), and renal outcomes among participants with or without OSA in the EMPA-REG OUTCOME trial. <p><b>Research Design and Methods: </b>Participants with diabetes and CVD were randomized to empagliflozin (10/25mg), or placebo daily in addition to standard of care. OSA was assessed by investigator-reports using MedDRA-18.0 and CV o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Increasing evidence has indicated that SGLT2i exerts protective effects on nephritis, nephrotic syndrome and nephrosis 25 , chronic liver disease 26 , and septicemia survival 27 . SGLT2i-use also demonstrated consistent heart and kidney protective effects in patients with obstructive sleep apnea 28 and chronic obstructive pulmonary disease 29 .…”
Section: Discussionmentioning
confidence: 87%
“…Increasing evidence has indicated that SGLT2i exerts protective effects on nephritis, nephrotic syndrome and nephrosis 25 , chronic liver disease 26 , and septicemia survival 27 . SGLT2i-use also demonstrated consistent heart and kidney protective effects in patients with obstructive sleep apnea 28 and chronic obstructive pulmonary disease 29 .…”
Section: Discussionmentioning
confidence: 87%
“…SGLT2i have been shown to reduce incident obstructive sleep apnea in two SGLT2i CVOTs based on adverse event reporting (304,305). However, it is not clear that the data collected on incident obstructive sleep apnea in these trials were complete or that the benefit is mediated through changes in weight.…”
Section: Obesity and Weight-related Comorbidities Particularly Nafld ...mentioning
confidence: 99%
“…In this way, SGLT2 inhibitors may decrease rostral-to-caudal fluid shifts in the recumbent sleep position, cardiac preload, and intrathoracic fluid retention; (iii) due to the modest increase in urinary frequency, manifested usually as nocturia, SGLT2 inhibitors could promote interrupted sleep cycles and suppress the duration of REM sleep (a higher risk period for OSA events); (iv) SGLT2 inhibitors can suppress circadian sympathetic nervous system activation and its related conditions (such as non-dipping pattern of hypertension, cardiac autonomic neuropathy, and stroke); (v) forced glucosuria after their administration can reduce the availability of glucose as an energy fuel. In this way other substrates are utilized, and less endogenous CO 2 production is expected, with less CO 2 to be removed by the respiratory tract; and (vi) modulation of arousal threshold, muscle compensation, and loop gain [78,[93][94][95][96][97][98].…”
Section: Pathophysiological Conceptsmentioning
confidence: 99%
“…A recent exploratory post-hoc analysis of the EMPA-REG OUTCOME trial demonstrated that about 6% of the population enrolled experienced OSA at baseline [100]. Patients with OSA were more likely to experience moderate to severe obesity (55.2% vs. 18.2%), had greater prevalence of CAD, longer duration of T2D, higher rates of insulin administration, and more prevalent use of antihypertensive therapies.…”
Section: Empagliflozinmentioning
confidence: 99%